High Density 3D Mapping and Ablation of Complex Cardiac Arrhythmias: Our Experience in NICVD (Bangladesh Heart Journal, 2021)
Background: Catheter ablation can be curative in patients with drug-refractory tachyarrhythmias. 3D electro anatomical mapping (EAM) is an established tool facilitating catheter ablation. This system is particularly valuable for mapping complex arrhythmias, which provide excellent assistance to catheter navigation, reduces fluoroscopy exposure, and also allow for the accurate placement of catheters. The Rhythmia Mapping System (RMS, Boston Scientific) is a novel system that allows for ultra-fast, high-density 3D mapping.Aim of this Study: The aim of this study was to find out the result of a high-density 3D mapping for the ablation of complex Cardiac Arrhythmias and to share our experiences.Methods: A total number of 44 patients of different tachyarrhythmias were scheduled for catheter ablation by Rhythmia Mapping System in National Institute of Cardiovascular Diseases, Bangladesh from 3rd February’2018 to 18th July’2019. During and after, the procedure all the cases were evaluated for different procedure parameters, acute success and in-hospital success.Results: Among the patients (28/44 male) 13 (25.55%) cases were atrial fibrillation, 6 (16.64%) cases were atrial flutter, 6 (16.64%) cases were atrial tachycardia, 2 (4.55%) cases were ventricular tachycardia, 11 (25%) cases were PVC and 6 (16.64%) cases were accessory pathway. The mean age was 38±4.5 years. In 25 (56.82%) of tachyarrhythmia patients, the mechanism was macro reentry/micro reentry, while in 19 (43.18%) cases the mechanism was increased automaticity. In all cases, the tachycardias were adequately mapped & proper identification of focus was done during the index procedure with the ultra-high density 3-D Rhythmia Mapping System (RMS). These all were successfully terminated by radiofrequency ablation, except one, which was one of the two cases of Ventricular tachycardia. With this system our study samples had a success rate of 98% with arrhythmia elimination. In patients of atrial fibrillation, all 4 pulmonary veins isolation were done. The mean mapping time was 28.6 ± 17 minutes, and the mean radiofrequency ablation time to arrhythmia termination was 3.2± 2.6 minutes. During our study only two out of 44 patients developed complications. One of the patients with atrial fibrillation developed cardiac tamponade and the other patient with PVC originating from Aortic cusp developed ischemic stroke. Fortunately, they were both managed accordingly. During hospital discharge, all the patients were free of tachyarrhythmia and were in sinus rhythm.Conclusions: This new automated ultrahigh-resolution mapping system allows accurate diagnosis of tachyarrhythmia circuits. Ablation of the focus resulted in high acute success.Bangladesh Heart Journal 2021; 36(2): 98-104